THE USE OF FIRST LANGUAGE (L1) IN EYL CLASSROOM : A Case Study at Three Elementary Schools in Tasikmalaya - Primary, Metty Agustine (2012)
This study focuses on the use of L1 in English for young learners (Teaching English to Young Learners). In this study, three English teachers and three classes of the third grade of three elementary schools in Tasikmalaya were involved as participants. The purpose of the study is to get insights in what stage (pre-, whilst, or post activities) of English teaching learning process that L1 is used, the functions of L1 in the teaching of English to young learners, and the teachers' reasons for using L1 in TEYL. Research design used in this study was a case study. The data were collected through fifteen times classroom observations and interviews with the three teacher respondents. Data from classroom observations were coded, categorized and analyzed based on the occurrence of L1 used by teachers in the English instructions. Data from interviews were also categorized based on the teachers' reasons for using L1 in the classrooms. The result of this study indicates that most of the teachers used L1 in all three stages of teaching process, pre-, whilst and post activities. This study confirms previous research which categorizes the functions of L1 into ten categories (Allwright, 1988) - asking questions, introducing new words, reviewing, giving information, giving directions, lecturing, praising, criticizing students, encouraging, and responding to students' activity or statement. Generally, the functions can be categorized into three purposes: instructional, managerial, and affective purposes. Furthermore, the reasons for L1 use include facilitating communication, facilitating teacher-student relationships, and facilitating the learning of L2. In conclusion, the use of L1 in TEYL can benefit students in learning English.